The Effect of Work Environment, Pressure, and Social Support on Employee Performance at PT. Tani Prima Makmur - Tauwi Tauwi (Green Inflation: International Journal of Management and Strategic Business Leadership, 2025)
The purpose of this study is to analyze the influence of the work environment, work pressure, and social support on the performance of employees at the palm oil processing factory of PT. Tani Prima Makmur. This research was conducted at the office of the palm oil processing factory located in Lerehoma, Anggaberi District, Konawe Regency. A questionnaire was used as the primary tool for data collection, with a Likert scale employed to measure the responses to various statements related to the work environment, work pressure, social support, and employee performance. Multiple linear regression analysis was applied to examine the relationships between the independent variables (work environment, work pressure, and social support) and the dependent variable (employee performance). The results of the t-test revealed that the significance value of the work pressure variable (X2) is 0.000, which is smaller than the 5% threshold (0.000 < 0.05), indicating that work pressure significantly affects employee performance. Similarly, the significance value for the social support variable (X3) is 0.000, which is also smaller than 0.05, suggesting that social support has a significant impact on employee performance. In contrast, the significance value for the work environment variable (X1) is 0.615, which is greater than 0.05 (0.615 > 0.05), indicating that the work environment does not significantly affect employee performance in this case. These findings suggest that while work pressure and social support are crucial factors influencing employee performance, the work environment may not play as significant a role in improving performance at PT. Tani Prima Makmur. The study highlights the importance of providing adequate support and managing work pressure to enhance employee productivity in the palm oil processing industry. Further research may explore other potential factors that could contribute to improving employee performance in similar contexts.